Episodic Memory and Executive Function Are Differentially Affected by Retests but Similarly Affected by Age in a Longitudinal Study of Normally-Aging Older Adults - Glisky, Elizabeth L.; Woolverton, Cindy B.; McVeigh, Katelyn S.; Grilli, Matthew D. (Frontiers in Aging Neuroscience, 2022)
Episodic memory and executive function are two cognitive domains that have been studied extensively in older adults and have been shown to decline in normally-aging older individuals. However, one of the problems with characterizing cognitive changes in longitudinal studies has been separating effects attributable to normal aging from effects created by repeated testing or practice. In the present study, 166 people aged 65 and older were enrolled over several years and tested at least 3 times at variable intervals (M=3.2 yrs). The cognitive measures were composite scores. Each composite was made up of five neuropsychological tests, previously identified through factor analysis. For one pair of composite scores, variance attributable to age was removed from each subtest through regression analyses before z-scores were computed, creating two age-corrected composites. A second pair of composites were not age-corrected. Using linear mixed-effects models, we first explored retest effects for each cognitive domain, independent of age, using the age-corrected composites. We then modeled aging effects using the age-uncorrected composites after subtracting out retest effects. Results indicated significant retest effects for memory but not for executive function, such that memory performance improved across the three testing sessions. When these practice effects were removed from the age-uncorrected data, effects of aging were evident for both executive and memory function with significant declines over time. We also explored several individual difference variables including sex, IQ, and age at the initial testing session and across time. Although sex and IQ affected performance on both cognitive factors at the initial test, neither was related to practice effects, although young-older adults tended to benefit from practice to a greater extent than old-older adults. In addition, people with higher IQs showed slower age-related declines in memory, but no advantages in executive function. These findings suggest that a) aging affects both memory and executive function similarly, b) higher IQ, possibly reflecting cognitive reserve, may slow age-related declines in memory, and c) practice through repeated testing enhances performance in memory particularly in younger-older adults, and may therefore mask aging effects if not taken into account.